A personality career test for public secondary schools using android application - Hamid, Su’aidi; Senan, Norhalina (Penerbit UTHM, 2021)
Personality test is a tool used to assess human personality which there are two types of personality tests that is self-report inventories and projective tests where most schools use self-report inventories by paper which is inefficient and require resources more than what can be achieved by using mobile android application instead. Existing applications of personality test in Google Play are not using the same inventory tests that are used within public schools which makes it not viable as a primary source for public schools. This project is about developing an android mobile application that helps user to determine their personality and narrow down some of the suggested types of career that suits the user’s personality. At the end of the test, the application will calculate the user scores and present 3 keywords that represents user personality instantly which saves time and resources required compared using paper-based method that public schools use. The methodology used to develop this project is Multimedia Content Development (MMCD) methodology to narrow down system requirements and user requirements that is suitable for mobile learning application. Testing phase is carried out amongst target user which is secondary school students and the subject matter expert of this project by using google form for testers to leave their review of their experience on using the application. The testing results for this project gained positive feedback from the testers with the score of 81.38% in System Usability Scale (SUS) score.